2012
DOI: 10.1504/ijlt.2012.046864
|View full text |Cite
|
Sign up to set email alerts
|

Usage reporting on recorded lectures using educational data mining

Abstract: Abstract:Most research of the use of recorded lectures by students is based on surveys. In this article we will report on the further analysis of student's use of recorded based on methodological triangulation. We will describe the process of data pre-processing where a number of data sources are combined after which the data is cleaned, removing outliers and data not relevant to the research.The analysis looks both at the data form a high level point of view and on the more detailed level for a single course.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 12 publications
2
27
1
Order By: Relevance
“…Analysis of video viewing data is a relatively recent trend and there is a small but increasing body of on-going research that focuses on the topic (e.g. Li et al 2015a, 2015b, Giannakos et al 2015, Giannakos et al 2014b, Kleftodimos & Evangelidis 2014a, b, Brooks et al 2013, Gorissen et al 2012, De Boer et al 2011. Thus, it is certainly a plus for a tool to provide more advanced analytics features but most importantly to provide the whole dataset of viewing and activity data that will enable researchers to conduct more elaborate data analysis by applying advanced statistical methods, visualizations and data mining algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of video viewing data is a relatively recent trend and there is a small but increasing body of on-going research that focuses on the topic (e.g. Li et al 2015a, 2015b, Giannakos et al 2015, Giannakos et al 2014b, Kleftodimos & Evangelidis 2014a, b, Brooks et al 2013, Gorissen et al 2012, De Boer et al 2011. Thus, it is certainly a plus for a tool to provide more advanced analytics features but most importantly to provide the whole dataset of viewing and activity data that will enable researchers to conduct more elaborate data analysis by applying advanced statistical methods, visualizations and data mining algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there is a growing interest in employing educational data mining techniques (EDM) to conduct the automatic analysis of learner performance and behavioral data in learning environments. Various experiments have been carried out in the EDM area that assess student learning performance, improve the learning process, guide student learning, provide feedback, adapt learning recommendations based on student learning behaviors, and evaluate learning materials and courseware [1,11,7]. An emerging trend in EDM is the use of text mining which is an extension of data mining to text data.…”
Section: Related Workmentioning
confidence: 99%
“…They found that students who used the hinting system achieved significantly better results than those who did not, and stayed active on the site longer. Gorissen et al [51] analyzed the interactions of students with the recorded lectures using educational data mining techniques. They found discrepancies as well as similarities between students' verbal reports and actual usage as logged by the recorded lecture servers.…”
Section: Edm Applications For Predicting and Evaluatingmentioning
confidence: 99%
“…However, some studies also used interaction traces [32,48], communication traces [28,56], and responses to satisfaction questionnaire [50] or combined between several types of data such as in [23,44,48,51]. Another approach that we found in [31] was to generate simulated data using a probability matrix in order to test several models.…”
Section: Edm Applications For Predicting and Evaluatingmentioning
confidence: 99%
See 1 more Smart Citation